2017
DOI: 10.1002/adma.201606206
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Blade‐Coated Multicolor Polymer Light‐Emitting Diodes for Optoelectronic Sensors

Abstract: A method to print two materials of different functionality during the same printing step is presented. In printed electronics, devices are built layer by layer and conventionally only one type of material is deposited in one pass. Here, the challenges involving printing of two emissive materials to form polymer light‐emitting diodes (PLEDs) that emit light of different wavelengths without any significant changes in the device characteristics are described. The surface‐energy‐patterning technique is utilized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
108
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(116 citation statements)
references
References 25 publications
0
108
0
4
Order By: Relevance
“…[16,39] The absence of film formation on low surface tension substrates has also been shown when coating at faster speeds, [19,[31][32][33] in the Landau-Levich regime. Solventsurface treatment combinations with higher contact angles lead to unsuccessful coatings, as solvent evaporation at the tip of the meniscus is suppressed, compromising solute supersaturation and precipitation.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 89%
“…[16,39] The absence of film formation on low surface tension substrates has also been shown when coating at faster speeds, [19,[31][32][33] in the Landau-Levich regime. Solventsurface treatment combinations with higher contact angles lead to unsuccessful coatings, as solvent evaporation at the tip of the meniscus is suppressed, compromising solute supersaturation and precipitation.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 89%
“…The ultrathin ECG sensor device provided stable operation in repeated bending/fatigue tests and was successfully attached to the body, which substantiated its potential to monitor ECG as a wearable biomedical device. Han et al simultaneously fabricated multicolor OLEDs via surface energy patterning (SEP) technology using a solution‐based polymer light‐emitting material . The authors demonstrated s‐pulse oximetry sensors using light reflected from the fingertip by s‐photoplethysmogram (PPG), using red and green PLEDs and silicon photodiodes, formed by blade coating, as light emitters and light detectors, respectively.…”
Section: Advanced Strategies For Wearable Smart Sensing Systems Basedmentioning
confidence: 99%
“…d) Photograph of the optoelectronic sensor that uses green and red PLEDs as the light source and a silicon PD as the light detector (the sensor is placed on top of the wrist for collecting the PPG signal). c,d) Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Advanced Strategies For Wearable Smart Sensing Systems Basedmentioning
confidence: 99%
“…To date, solution processes have been widely used for fabricating QD films because they involve mild conditions and easy operation, such as contact printing, spin coating, screen printing, roll‐to‐roll coating, blade coating, inkjet printing, and others . However, these approaches normally suffer from the limitations of either high‐cost or low film quality.…”
Section: Summary Of the Performance Of The As‐prepared Qled Devices (mentioning
confidence: 99%